2021
DOI: 10.1093/bjs/znab395.050
|View full text |Cite
|
Sign up to set email alerts
|

P054 reduction of Failure Rates After Incisional Hernia Repair by Adding a Prophylactic Mesh

Abstract: Aim “Can a mesh reduce failure rates after closure of a hernia defect?” Material and Methods “Porcine abdominal walls and bovine flanks were used as model tissues. After preparation, a 15 cm long incision was placed in the linea alba of the porcine abdominal wall. An additional round 5 cm defect was punched in the middle of the incision. The bovine flank was prepared in a similar manner. The incisions with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In this study, the VAS pain score of the trial group was markedly higher than that of the control group at 1 week, 4 weeks, and 6 months after therapy; it showed that using small incision reduction and suture linked with functional appliance to treat sufferers with irreducible ADD of the TMJ could reduce the degree of pain and duration of pain, played a good role in promoting the prognosis of sufferers, and improved the quality of life of sufferers [ 24 26 ]. It was consistent with the study of small incision reduction and suture in the treatment of ADD of the TMJ, relieving pain and improving joint function by Xing et al [ 27 ].…”
Section: Discussionmentioning
confidence: 97%
“…In this study, the VAS pain score of the trial group was markedly higher than that of the control group at 1 week, 4 weeks, and 6 months after therapy; it showed that using small incision reduction and suture linked with functional appliance to treat sufferers with irreducible ADD of the TMJ could reduce the degree of pain and duration of pain, played a good role in promoting the prognosis of sufferers, and improved the quality of life of sufferers [ 24 26 ]. It was consistent with the study of small incision reduction and suture in the treatment of ADD of the TMJ, relieving pain and improving joint function by Xing et al [ 27 ].…”
Section: Discussionmentioning
confidence: 97%